Spirit of Indian Constitution and Right to Food (International Journal of Food and Nutritional Sciences, 2022)
The right to food is a fundamental human right recognized by the United Nations. It is the right of every person to have access to sufficient, safe, nutritious, and culturally acceptable food to meet their dietary needs and food preferences for an active and healthy life. The importance of the right to food cannot be overstated. Access to food is essential for the survival and well-being of individuals and communities. Without adequate access to food, people suffer from malnutrition, hunger, and related health problems. The right to food is also closely linked to other human rights, including the right to life, the right to health, and the right to work